Characterization of the lipopolysaccharide of Stenotrophomonas rhizophila, a representative of Antarctica - Brovarska, O.S.; Varbanets, L.D. (Problems of Environmental Biotechnology, 2023)
SR-form LPS preparations were obtained from S. rhizophila cells, which differed in monosaccharide and fatty acid composition, had identical antigens, but had high pyrogenicity.